Pelatihan Penyusunan Buku Kas Sebagai Peningkatan Mutu UMKM dalam Bidang Keuangan - Dwi Kurniani; Nugraeni Nugraeni (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
UMKM is an economic platform for the community which is a basic component in the development of economic pillars starting from the lowest level, small and medium enterprises (UKM/UMKM) are types of companies in Indonesia which are owned by individuals or business entities in accordance with the criteria set by Law No. 20 of 2008. UMKM is able to defined as business run by individuals, households, or small-sized business entities. The classification of UMKM is based on limits on annual revenue turnover, total assets, and number of employees. The development and quality improvement needs to get serious support for its further growth, this is not only in terms of capital and ease of doing business, but also needs to be done in terms of management up to the ability of the perpetrators, one of that the UMKM perpetrators must learn about management, especially in financial management, starting with simple things such as preparing a cash book. Most UMKM are run by individuals who do not have special skills. UMKM run as they are and do not have a good financial planning system and financial management system, this is one of the weaknesses of UMKM, so they cannot make plans for future business development. The cash book preparation training aims to increase the financial management capacity of Micro, Small and Medium Enterprises (UMKM). The training method is designed to provide a basic understanding of accounting principles, financial statement preparation techniques, and practical applications that are relevant to the needs of UMKM. This training program is expected to improve the quality and financial performance of UMKM, so that they can be more competitive and sustainable in the market.